Assessing environmental assets for health promotion program planning: a practical framework for health promotion practitioners - Andrew E. Springer; Alexandra E. Evans (Tabriz University of Medical Sciences, 2016)
Conducting a health needs assessment is an important if not essential first step for health promotion planning. This paper explores how health needs assessments may be further strengthened for health promotion planning via an assessment of environmental assets rooted in the multiple environments (policy, information, social and physical environments) that shape health and behavior. Guided by a behavioral-ecological perspective- one that seeks to identify environmental assets that can influence health behavior, and an implementation science perspective- one that seeks to interweave health promotion strategies into existing environmental assets, we present a basic framework for assessing environmental assets and review examples from the literature to illustrate the incorporation of environmental assets into health program design. Health promotion practitioners and researchers implicitly identify and apply environmental assets in the design and implementation of health promotion interventions;this paper provides foundation for greater intentionality in assessing environmental assets for health promotion planning.